STRESS COPING SKILLS IN ADOLESCENT HIGH SCHOOL STUDENTS - Morales Salinas, Brenda Guadalupe (2015)
Adolescence entails a reorganization of social, interpersonal interactions (Ávila, Heredia, Gómez & Martínez, 2006; Cardozo & Alderete, 2008), which generates stress (Frydenberg & Lewis, 2009). To deal with it, a variety of actions and cognitions are used, which prepare us to tolerate or minimize the effects produced by it (González, Montoya, Martina and Bernabeu,2002). The purpose of this research is to describe the coping strategies used by adolescent high school students, making comparisons by sex and age. The work was done with 724 adolescents: 413 females and 311 males; ranging between 14 and 17 years of age, from Valle de Toluca, Estado de México. The Adolescent Coping Scale (ACS), developed by Frydenberg and Lewis (2000) was applied. The results obtained regarding the strategies used by adolescents in stressful situations are: to work hard and achieve, seek relaxing diversions, and worry. Females use more strategies focused on solving the problem, and they handle their emotions, unlike males who evade the problem and are more emotionally reserved. Regarding the age comparison, it was found that 16-year olds employ problem-evasion strategies. The implications of this study are discussed.